Preparation method of positive electrode material
The preparation of sodium ion battery positive electrode material through ultrasonic treatment method solves the performance attenuation problem caused by airflow crushing, and achieves higher capacity retention and excellent electrochemical performance.
Patent Information
- Application Number
- CN202411812307.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing sodium ion battery positive electrode material is severely damaged by airflow crushing during the crushing process, resulting in low capacity, severe attenuation of circulation performance and electrical conductivity.
Ultrasonic treatment method is used to replace traditional airflow pulverization. High-quality positive electrode material is prepared by mixing sodium, iron, phosphorus, carbon and solvent, drying, calcining and sonication after drying, and controlling the particle size of the precursor.
The cathode material prepared by ultrasonic treatment method is uniform in particle size, excellent electrochemical performance, high capacity retention, and significantly improved circulation performance and electrical conductivity. It is suitable for room-temperature sodium ion batteries for large-scale energy storage applications.
Smart Images

Figure CN119612477A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a method for preparing a positive electrode material. Background Art
[0002] As the application of lithium-ion batteries in electric vehicles increases, the demand for lithium is also increasing greatly, but the reserves of lithium are limited and unevenly distributed, which will undoubtedly become an important problem for the development of long-life energy storage batteries for large-scale energy storage. Based on this background, we urgently need to develop new long-life energy storage devices.
[0003] Since sodium has similar physical and chemical properties and storage mechanisms to lithium, and has abundant reserves and is widely distributed in the earth's crust, the development of room-temperature sodium-ion battery technology for large-scale energy storage applications is of great strategic significance. In recent years, this technology has received widespread attention from research groups around the world.
[0004] At present, there are three main types of commercial sodium-ion battery cathode materials: layered oxide cathode materials, polyanion cathode materials, and Prussian cathode materials; among them, polyanion cathode materials have attracted much attention for their excellent cycle performance and safety performance. When using polyanion cathode materials, they need to have a suitable particle size to achieve excellent electrochemical performance. When the existing technology crushes polyanion cathode materials, air flow crushing is often the main method, but air flow crushing causes serious damage to the cathode material particles, resulting in low capacity of the crushed cathode material, and serious attenuation of cycle performance and material conductivity. Therefore, the development of a suitable synthesis method is crucial to the marketization and large-scale application of sodium-ion battery cathode materials. Summary of the invention
[0005] The present application provides a method for preparing a positive electrode material, aiming to solve the problem that the positive electrode material obtained by the existing preparation process has low capacity, and the cycle performance and material conductivity are seriously attenuated.
[0006] The present application provides a method for preparing a positive electrode material, comprising the following steps:
[0007] (1) mixing a sodium source, an iron source, a phosphorus source, a carbon source and a solvent, and drying to obtain a precursor;
[0008] (2) Calcining the precursor of step (1), and subjecting the calcined product to ultrasonic treatment to obtain the positive electrode material.
[0009] The preparation method of the positive electrode material described in the present application uses ultrasonic treatment to treat the positive electrode material product, so that the particle size of the precursor can be effectively regulated.
[0010] According to some embodiments of the method for preparing a positive electrode material described in the present application, in step (1), the sodium source includes one or more of sodium dihydrogen phosphate, sodium phosphate, sodium carbonate, sodium nitrate, sodium oxalate, sodium acetate, sodium sulfate and sodium hydroxide.
[0011] According to some embodiments of the method for preparing a positive electrode material described in the present application, the iron source includes one or more of ferric nitrate, ferrous nitrate, ferric sulfate, ferrous sulfate, ferric chloride, ferrous chloride, ferrous oxalate, ferrous oxalate, ferric acetate, ferric phosphate and ferric pyrophosphate.
[0012] According to some embodiments of the method for preparing a positive electrode material described in the present application, in step (1), the phosphorus source includes one or more of sodium dihydrogen phosphate, sodium phosphate, sodium monohydrogen phosphate, phosphoric acid and ammonium dihydrogen phosphate.
[0013] According to some embodiments of the method for preparing a positive electrode material described in the present application, in step (1), the carbon source includes one or more of soluble starch, ascorbic acid, citric acid, sucrose and glucose.
[0014] According to some embodiments of the method for preparing a positive electrode material described in the present application, in step (1), the solvent includes water and / or ethanol.
[0015] According to some embodiments of the method for preparing a positive electrode material described in the present application, in step (1), the molar ratio of the sodium element in the sodium source to the iron element in the iron source is (3-4):3.
[0016] According to some embodiments of the method for preparing a positive electrode material described in the present application, the molar ratio of the sodium element in the sodium source to the phosphorus element in the phosphorus source is (1-3):1.
[0017] According to some embodiments of the method for preparing a positive electrode material described in the present application, the molar ratio of the sodium element in the sodium source to the carbon element in the carbon source is (3-5):1.
[0018] According to some embodiments of the method for preparing a positive electrode material described in the present application, the drying is spray drying.
[0019] According to some embodiments of the method for preparing a positive electrode material described in the present application, the spray drying temperature is 100-110°C.
[0020] According to some embodiments of the method for preparing a positive electrode material described in the present application, in step (2), the calcination includes a first stage calcination and a second stage calcination.
[0021] According to some embodiments of the method for preparing a positive electrode material described in the present application, the temperature of the first-stage calcination is 280-320° C., and the time of the first-stage calcination is 2.5-3.5 hours.
[0022] According to some embodiments of the method for preparing a positive electrode material described in the present application, the temperature of the second stage calcination is 500-600° C., and the time of the second stage calcination is 8-12 hours.
[0023] According to some embodiments of the method for preparing a positive electrode material described in the present application, the heating rate from the first stage calcination to the second stage calcination is 1-3° C. / min.
[0024] According to some embodiments of the method for preparing a positive electrode material described in the present application, the frequency of the ultrasonic treatment is 70-90Khz, and the time of the ultrasonic treatment is 0.8-1.2h.
[0025] According to some embodiments of the method for preparing a positive electrode material described in the present application, the particle size of the positive electrode material is 5.0-6.0 μm. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a SEM image of the positive electrode material prepared in Example 1 of the present application;
[0027] Figure 2 This is a SEM image of the positive electrode material prepared in Comparative Example 1 of the present application;
[0028] Figure 3 This is a SEM image of the positive electrode material prepared in Comparative Example 2 of the present application. DETAILED DESCRIPTION
[0029] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0030] The technical solution of the present application is described in detail below in conjunction with specific embodiments and drawings.
[0031] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0032] The present application provides a method for preparing a positive electrode material, comprising the following steps:
[0033] (1) mixing a sodium source, an iron source, a phosphorus source, a carbon source and a solvent, and drying to obtain a precursor;
[0034] (2) Calcining the precursor of step (1), and subjecting the calcined product to ultrasonic treatment to obtain the positive electrode material.
[0035] In the prior art, air flow pulverization is often used as the main method for pulverizing polyanion positive electrode materials, but air flow pulverization causes serious damage to the positive electrode material particles, resulting in low capacity of the crushed positive electrode material, and serious attenuation of the cycle performance and material conductivity. The present application uses ultrasonic treatment to replace the traditional air flow pulverization method. On the basis of pulverizing the positive electrode material, the particles are mixed more evenly without damaging the positive electrode material, so that the battery prepared by the method has better electrochemical performance.
[0036] In some embodiments of the present application, in step (1), the sodium source includes one or more of sodium dihydrogen phosphate, sodium phosphate, sodium carbonate, sodium nitrate, sodium oxalate, sodium acetate, sodium sulfate and sodium hydroxide.
[0037] In some embodiments of the present application, the iron source includes one or more of ferric nitrate, ferrous nitrate, ferric sulfate, ferrous sulfate, ferric chloride, ferrous chloride, ferrous oxalate, ferrous oxalate, ferrous acetate, ferric phosphate and ferric pyrophosphate.
[0038] In some embodiments of the present application, in step (1), the phosphorus source includes one or more of sodium dihydrogen phosphate, sodium phosphate, sodium monohydrogen phosphate, phosphoric acid and ammonium dihydrogen phosphate.
[0039] In some embodiments of the present application, the carbon source includes one or more of soluble starch, ascorbic acid, citric acid, sucrose and glucose.
[0040] In some embodiments of the present application, the solvent includes water and / or ethanol.
[0041] In some embodiments of the present application, the molar ratio of the sodium element in the sodium source to the iron element in the iron source is (3-4):3, for example, 3:3, 3.5:3, 4:3, etc.
[0042] In some embodiments of the present application, the molar ratio of the sodium element in the sodium source to the phosphorus element in the phosphorus source is (1-3):1, for example, 1:1, 2:1, 3:1, etc.
[0043] In some embodiments of the present application, the molar ratio of the sodium element in the sodium source to the carbon element in the carbon source is (3-5):1, for example, 3:1, 4:1, 5:1, etc.
[0044] In some embodiments of the present application, the drying is spray drying. Spray drying has a fast drying speed, a simple process, and is suitable for continuous production.
[0045] In some embodiments of the present application, the spray drying temperature is 100-110°C, for example, 100°C, 105°C, 108°C, 110°C, etc.
[0046] In some embodiments of the present application, in step (2), the calcination includes a first stage calcination and a second stage calcination.
[0047] Calcination is carried out in two stages to improve the physical properties of the positive electrode material. The first calcination is carried out at a low temperature to allow the material to be fully pyrolyzed; the second calcination is carried out at a higher temperature to control the crystal structure of the electrode material by introducing specific elements, thereby improving the capacity and energy density of the battery and extending the service life of the battery; the calcination process can reduce the thermal runaway of the battery, improve the safety of the battery, and at the same time reduce the internal resistance and polarization phenomenon, ensuring that the battery has better discharge performance and cycle life; Calcination is carried out in two stages to eliminate abnormal expansion and improve compressive strength and durability.
[0048] In some embodiments of the present application, the temperature of the first stage calcination is 280-320°C, such as 280°C, 300°C, 320°C, etc., and the time of the first stage calcination is 2.5-3.5h, such as 2.5h, 3h, 3.5h, etc. Within this temperature range, the material can be fully pyrolyzed.
[0049] In some embodiments of the present application, the temperature of the second stage calcination is 500-600°C, such as 500°C, 520°C, 550°C, 580°C, 600°C, etc., and the time of the second stage calcination is 8-12h, such as 8h, 9h, 10h, 11h, 12h, etc. Selecting this temperature range allows the material to fully react chemically without destroying the structure of the material. Too high a calcination temperature may cause structural damage to the material, reduce the capacity and cycle life of the battery, while too low a calcination temperature may cause incomplete chemical reactions inside the battery, affecting the performance and safety of the battery.
[0050] In some embodiments of the present application, the heating rate from the first stage calcination to the second stage calcination is 1-3°C / min, for example, 1°C / min, 2°C / min, 3°C / min, etc.
[0051] In some embodiments of the present application, the frequency of the ultrasonic treatment is 70-90Khz, such as 70Khz, 75Khz, 80Khz, 85Khz, 88Khz, 90Khz, etc., and the time of the ultrasonic treatment is 0.8-1.2h, such as 0.8h, 1.0h, 1.2h, etc. The setting selection of the frequency of the present application depends on the particle size and dispersion requirements of the powder.
[0052] In some embodiments of the present application, the particle size of the positive electrode material is 5.0-6.0 μm, for example, 5.0 μm, 5.5 μm, 6.0 μm, etc.
[0053] Example 1
[0054] A method for preparing a positive electrode material comprises the following steps:
[0055] (1) dissolving sodium dihydrogen phosphate, ferric nitrate, phosphoric acid and citric acid in distilled water, and spray drying at 105° C. to obtain a yellow precursor powder; wherein the molar ratio of sodium element in sodium dihydrogen phosphate to iron element in ferric nitrate is 4:3, the molar ratio of sodium element in sodium dihydrogen phosphate to phosphorus element in phosphoric acid is 2:1, and the molar ratio of sodium element in sodium dihydrogen phosphate to carbon element in citric acid is 4:1;
[0056] (2) sintering the precursor powder of step (1) at 300° C. for 3 h under an inert atmosphere, then heating to 550° C. at a heating rate of 2° C. / min, and sintering at this temperature for 10 h to obtain a positive electrode material product;
[0057] (3) The cathode material product of step (2) is ultrasonically crushed at 80 kHz for 1 h to obtain a cathode material with a D50 of 5 μm.
[0058] Example 2
[0059] The only difference between Example 2 and Example 1 is that the frequency of ultrasonic treatment in Example 2 is 70Khz.
[0060] The specific operations are:
[0061] A method for preparing a positive electrode material comprises the following steps:
[0062] (1) dissolving sodium dihydrogen phosphate, ferric nitrate, phosphoric acid and citric acid in distilled water, and spray drying at 105° C. to obtain a yellow precursor powder; wherein the molar ratio of sodium element in sodium dihydrogen phosphate to iron element in ferric nitrate is 4:3, the molar ratio of sodium element in sodium dihydrogen phosphate to phosphorus element in phosphoric acid is 2:1, and the molar ratio of sodium element in sodium dihydrogen phosphate to carbon element in citric acid is 4:1;
[0063] (2) sintering the precursor powder of step (1) at 300° C. for 3 h under an inert atmosphere, then heating to 550° C. at a heating rate of 2° C. / min, and sintering at this temperature for 10 h to obtain a positive electrode material product;
[0064] (3) The cathode material product of step (2) was ultrasonically crushed at 70 kHz for 1 h to obtain a cathode material with a D50 of 5.2 μm.
[0065] Example 3
[0066] The only difference between Example 3 and Example 1 is that the frequency of ultrasonic treatment in Example 3 is 90Khz.
[0067] The specific operations are:
[0068] A method for preparing a positive electrode material comprises the following steps:
[0069] (1) dissolving sodium dihydrogen phosphate, ferric nitrate, phosphoric acid and citric acid in distilled water, and spray drying at 105° C. to obtain a yellow precursor powder; wherein the molar ratio of sodium element in sodium dihydrogen phosphate to iron element in ferric nitrate is 4:3, the molar ratio of sodium element in sodium dihydrogen phosphate to phosphorus element in phosphoric acid is 2:1, and the molar ratio of sodium element in sodium dihydrogen phosphate to carbon element in citric acid is 4:1;
[0070] (2) sintering the precursor powder of step (1) at 300° C. for 3 h under an inert atmosphere, then heating to 550° C. at a heating rate of 2° C. / min, and sintering at this temperature for 10 h to obtain a positive electrode material product;
[0071] (3) The cathode material product of step (2) was ultrasonically crushed at 90 kHz for 1 h to obtain a cathode material with a D50 of 5.8 μm.
[0072] Comparative Example 1
[0073] The only difference between Comparative Example 1 and Example 1 is that the crushing method of the positive electrode material product in Comparative Example 1 is different from that in Example 1.
[0074] The specific operations are:
[0075] A method for preparing a positive electrode material comprises the following steps:
[0076] (1) dissolving sodium dihydrogen phosphate, ferric nitrate, phosphoric acid and citric acid in distilled water, and spray drying at 105° C. to obtain a yellow precursor powder; wherein the molar ratio of sodium element in sodium dihydrogen phosphate to iron element in ferric nitrate is 4:3, the molar ratio of sodium element in sodium dihydrogen phosphate to phosphorus element in phosphoric acid is 2:1, and the molar ratio of sodium element in sodium dihydrogen phosphate to carbon element in citric acid is 4:1;
[0077] (2) sintering the precursor powder of step (1) at 300° C. for 3 h under an inert atmosphere, then heating to 550° C. at a heating rate of 2° C. / min, and sintering at this temperature for 10 h to obtain a positive electrode material product;
[0078] (3) The positive electrode material product of step (2) is subjected to air flow crushing to obtain a positive electrode material with a D50 of 3.9 μm.
[0079] Comparative Example 2
[0080] The only difference between Comparative Example 2 and Example 1 is that the positive electrode material product is not crushed in Comparative Example 2.
[0081] The specific operations are:
[0082] A method for preparing a positive electrode material comprises the following steps:
[0083] (1) dissolving sodium dihydrogen phosphate, ferric nitrate, phosphoric acid and citric acid in distilled water, and spray drying at 105° C. to obtain a yellow precursor powder; wherein the molar ratio of sodium element in sodium dihydrogen phosphate to iron element in ferric nitrate is 4:3, the molar ratio of sodium element in sodium dihydrogen phosphate to phosphorus element in phosphoric acid is 2:1, and the molar ratio of sodium element in sodium dihydrogen phosphate to carbon element in citric acid is 4:1;
[0084] (2) The precursor powder of step (1) was sintered at 300° C. for 3 h under an inert atmosphere, then heated to 550° C. at a heating rate of 2° C. / min, and sintered at this temperature for 10 h to obtain a positive electrode material product.
[0085] Performance study of the positive electrode materials prepared in Example 1 and Comparative Examples 1-2 of the present application:
[0086] The SEM images of the positive electrode materials prepared in Example 1 and Comparative Examples 1-2 are shown in FIG. Figure 1 , Figure 2 and Figure 3 As shown:
[0087] from Figure 1-Figure 3 It can be seen that the positive electrode material product of Example 1 is obviously broken, but the particle size of the fragments is roughly 1 / 2 of the original. The powder of Comparative Example 1 is severely broken, with a wide particle size distribution and fine debris. The powder of Comparative Example 2 is not broken and has a smooth surface.
[0088] The materials prepared in Example 1 and Comparative Examples 1-2 were used as positive electrode materials. The positive electrode material, carbon black conductive agent and binder PVDF were added to NMP in a mass ratio of 90:5:5 and mixed evenly to prepare a positive electrode slurry for the battery. The solid content of the slurry was 45%. The slurry was coated on an aluminum foil with a thickness of 10 um, and the positive electrode sheet was made after vacuum drying and rolling. The sodium metal sheet was used as the negative electrode, and a solution of 1.15M NaPF6 and EC:DMC (1:1 vol%) was used as the electrolyte to assemble a button battery.
[0089] The button cell prepared above was tested using a Blue Electric battery testing system at a test temperature of 25°C and a test voltage of 1.5V. The charge and discharge capacity and first efficiency of the battery at 0.1C were tested, and the battery was cycled at 1C for 200 weeks. The discharge capacity at the 200th week was divided by the discharge capacity at the first week to obtain the cycle retention rate for 200 weeks. The test results are shown in Table 1.
[0090] Table 1
[0091] project Charging capacity (mAh / g) Discharge capacity (mAh / g) First effect 200cyc capacity retention rate Example 1 115 106 92.17% 97.50% Comparative Example 1 113 100 88.50% 94.30% Comparative Example 2 114.6 102 89.00% 97.12%
[0092] It can be seen from Table 1 that the button-type battery prepared by the positive electrode material described in Example 1 of the present application has an initial charge efficiency of 92.17%, and a 200cyc capacity retention rate of 97.50%, which are better than the button-type battery performance obtained by conventional airflow milling and un-crushed positive electrode materials. At the same time, the charge performance of the positive electrode material obtained by airflow milling is not as good as that of the un-crushed one, that is, airflow milling will reduce the performance of the positive electrode material.
[0093] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. A method for preparing a positive electrode material, characterized in that: The following steps are involved: (1) mixing a sodium source, an iron source, a phosphorus source, a carbon source and a solvent, and drying to obtain a precursor; (2) Calcining the precursor of step (1), and subjecting the calcined product to ultrasonic treatment to obtain the positive electrode material.
2. The method for preparing the positive electrode material according to claim 1, characterized in that: In step (1), the sodium source includes one or more of sodium dihydrogen phosphate, sodium phosphate, sodium carbonate, sodium nitrate, sodium oxalate, sodium acetate, sodium sulfate and sodium hydroxide; And / or, the iron source includes one or more of ferric nitrate, ferrous nitrate, ferric sulfate, ferrous sulfate, ferric chloride, ferrous chloride, ferrous oxalate, ferrous oxalate, ferric acetate, ferric phosphate and ferric pyrophosphate.
3. The method for preparing the positive electrode material according to claim 1, characterized in that: In step (1), the phosphorus source includes one or more of sodium dihydrogen phosphate, sodium phosphate, sodium monohydrogen phosphate, phosphoric acid and ammonium dihydrogen phosphate; and / or, the carbon source comprises one or more of soluble starch, ascorbic acid, citric acid, sucrose and glucose; And / or, the solvent comprises water and / or ethanol.
4. The method for preparing the positive electrode material according to claim 1, characterized in that: The molar ratio of the sodium element in the sodium source to the iron element in the iron source is (3-4):
3.
5. The method for preparing the positive electrode material according to claim 1, characterized in that: The molar ratio of the sodium element in the sodium source to the phosphorus element in the phosphorus source is (1-3):1; And / or, the molar ratio of the sodium element in the sodium source to the carbon element in the carbon source is (3-5):
1.
6. The method for preparing the positive electrode material according to claim 1, characterized in that: The drying is spray drying; Preferably, the spray drying temperature is 100-110°C.
7. The method for preparing the positive electrode material according to claim 1, characterized in that: In step (2), the calcination includes a first stage calcination and a second stage calcination; Preferably, the temperature of the first stage calcination is 280-320°C, and the time of the first stage calcination is 2.5-3.5h; Preferably, the temperature of the second stage calcination is 500-600° C., and the time of the second stage calcination is 8-12 hours.
8. The method for preparing the positive electrode material according to claim 7, characterized in that: The heating rate from the first stage calcination to the second stage calcination is 1-3°C / min.
9. The method for preparing the positive electrode material according to claim 1, characterized in that: The frequency of the ultrasonic treatment is 70-90Khz, and the time of the ultrasonic treatment is 0.8-1.2h.
10. The method for preparing the positive electrode material according to claim 1, characterized in that: The particle size of the positive electrode material is 5.0-6.0 μm.
Citation Information
Patent Citations
Silicon oxide-graphene coated high-nickel lithium battery anode material and preparation method
CN108390037A
Preparation method and application of ferric sodium pyrophosphate positive electrode material
CN117819512A
Preparation method of sodium ion battery positive electrode material
CN118637581A